Pengaruh Densitas Terhadap Kuat Tekan Pada Pembuatan Paving Block Dengan Penambahan Goni Plastik - Harahap, Sarah Aprilia; Masthura, Masthura; Jumiati, Ety (Rekayasa Material, Manufaktur dan Energi, 2026)
This study aims to determine the effect of adding plastic jute on the physical and mechanical properties of paving blocks, as well as to determine the optimal mixture composition. Plastic jute is used as an additional material in the paving block mixture along with sand and cement. Three composition variations were used in this study: Sample A (1% plastic jute, 64% sand, 35% cement), Sample B (3% plastic jute, 62% sand, 35% cement), and Sample C (5% plastic jute, 60% sand, 35% cement). Tests were conducted on the density and compressive strength of the paving blocks. The test results showed that Sample A had the highest density (1886.57 kg/m³), a compressive strength of 10 Mpa. These values meet SNI standards and indicate the best quality compared to other samples. Samples B and C have lower values, especially in water absorption and compressive strength. Thus, the addition of plastic jute significantly affects the quality of paving blocks, and the most optimal composition is found in Sample A. The use of plastic jute not only improves the characteristics of paving blocks but also helps reduce plastic waste in the environment.